Haunted Mustache - McGee, Joe; Skaffa, Teo (New York Aladdin, 2021)
Fifth-graders Parker and Lucas get more than they bargained for when they seek to debunk one of Wolver Hollow's greatest legends about a haunted mustache that, every year on the anniversary of its owner's death, seeks a lip to claim as its own.
Ages 7-10.
Case binding.
Perfect binding.
112419
Keywords: Mustaches -- Juvenile fiction; Legends -- Juvenile fiction; Friendship -- Juvenile fiction; Horror stories; Mystery and detective stories; Humorous stories; Monsters; Social Themes; Children's stories; Horror fiction; Detective and mystery fiction; Fiction; Humorous fiction; Juvenile works; Ghost stories